Fisheries jurisdiction cases - International Court of Justice (The Hague : ICJ, 1975)
2 vols
Keywords: Foreign fishing -- Germany; Germany (West) -- Boundaries -- Iceland; Great Britain -- Boundaries -- Iceland; Iceland -- Boundaries -- Germany (West).; Iceland -- Boundaries -- Great Britain